Revitalisasi Taman Pengajian Al-Quran Masjid Al-Mutaherin melalui Program Kuliah Kerja Nyata Pendidikan - Pasha, Dina Ike Wiranita; Wijayanti, Dyah Ayu Woro Schindy; Omolu, Fikriani Aminun (Lembaga Penelitian dan Pengabdian Pada Masyarakat, 2024)
Taman Pendidikan al-Quran (TPQ) is a non-formal educational institution focusing on Quranic learning and values for children. Its presence is crucial for introducing and instilling Quranic values at an early age. TPQ plays a vital role in nurturing children's spiritual, intellectual, and emotional development. It also aids in building character and reducing educational disparities. KKN-Dik, a program by Universitas Muhammadiyah Surakarta, aims to revitalize TPQ activities and engage the community in teaching Quranic studies. The activities include teaching Quranic recitation, holding discussions, and involving students in teaching, ensuring the continuation of Quranic education beyond the program's duration.